2020
DOI: 10.1128/jvi.00048-20
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus and DNA Vaccines Expressing Zika Virus Nonstructural Protein 1 Induce Substantial but Not Sterilizing Protection against Zika Virus Infection

Abstract: The nonstructural protein 1 (NS1) of several flaviviruses, including West Nile, dengue, and yellow fever viruses, is capable of inducing variable degrees of protection against flavivirus infection in animal models. However, the immunogenicity of NS1 protein of Zika virus (ZIKV) is less understood. Here, we determined the efficacy of ZIKV NS1-based vaccine candidates using two delivery platforms, methyltransferase-defective recombinant vesicular stomatitis virus (mtdVSV) and a DNA vaccine. We first show that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…When this vaccine was administered by the IM route to Ifnar −/− (interferon-αβ receptor knockout) mice, with boosting two and five weeks later, four/five mice developed high levels of NS1-specific antibodies. However, all of the mice developed severe disease after a 10 5 PFU ZIKV challenge [107]. Additional studies suggest an NS1 DNA vaccine can confer protection against ZIKV infection in BALB/c mice as long as NS1 is effectively secreted.…”
Section: Subunit Vaccine Candidatesmentioning
confidence: 91%
See 1 more Smart Citation
“…When this vaccine was administered by the IM route to Ifnar −/− (interferon-αβ receptor knockout) mice, with boosting two and five weeks later, four/five mice developed high levels of NS1-specific antibodies. However, all of the mice developed severe disease after a 10 5 PFU ZIKV challenge [107]. Additional studies suggest an NS1 DNA vaccine can confer protection against ZIKV infection in BALB/c mice as long as NS1 is effectively secreted.…”
Section: Subunit Vaccine Candidatesmentioning
confidence: 91%
“…In contrast, intranasal inoculation of the rVSV vaccine expressing only NS1 induced high levels of anti-NS1 antibodies, a T-cell response, and partial protection against ZIKV viremia in BALB/c mice. The vaccine given by the IM route did not protect Ifnar1 -/mice against a 10 5 PFU ZIKV challenge, while a 10 3 PFU challenge caused viremia and weight loss [107]. Alternatively, a ZIKV-NS1 vaccine was generated using a modified vaccinia Ankara (MVA) vector and was able to protect 100% of IM-vaccinated CD-1/ICR mice from IC challenge [116].…”
Section: Vectored Vaccine Candidatesmentioning
confidence: 99%
“…Thus, a single mutation (such as D1762A) in the MTase catalytic site abolished both G-N-7 and 29-O methylations (28,36). Previously, we showed that rVSV-D1762A is the most attenuated virus among all the mtdVSVs (26), and the rVSV-D1762A backbone has been recently used as a vector to deliver Zika virus antigen (37). Functionally, G-N-7 methylation is essential for mRNA stability and viral protein translation, whereas 29-O methylation serves as a molecular signature for host innate immunity to discriminate self from nonself RNA (27,38).…”
Section: Discussionmentioning
confidence: 99%
“…Methyltransferase defective (mtd) rVSVs expressing either the ZIKV pre-membrane protein (mtdVSV-ZIKVprM) or the pre-membrane protein, in addition to the envelope and non-structural 1 (NS1) proteins (mtdVSV-ZIKVprM-E-NS1), were able to elicit potent humoral and cellular immune responses and protect BALB/c and A129 mice from disease associated with ZIKV challenge. Interestingly, a vaccine expressing only NS1, mtdVSV-ZIKVNS1, was able to partially protect A129 and IFNAR -/- mice from ZIKV challenge, likely owing to a robust T cell response since a neutralizing antibody response was absent [ 131 , 132 ].…”
Section: Vsv As a Vaccine Vectormentioning
confidence: 99%